Fluorocarbene, fluoroolefin, and fluorocarbyne complexes of Rh. Issue 4 (23rd February 2017) - Pell, Christopher J.; Zhu, Yanjun; Huacuja, Rafael; Herbert, David E.; Hughes, Russell P.; Ozerov, Oleg V.
Abstract : The manuscript reports a series of complexes of small perfluorocarbon ligands with the (PNP)Rh fragment, analysis of their electronic structure, and comparison to the hydrocarbon analogues and complexes of CO and NO + . Abstract : The manuscript reports the synthesis, characterization, and analysis of electronic structure in a series of complexes of small perfluorocarbon ligands with the (PNP)Rh fragment (where PNP is a diarylamido/bis(phosphine) pincer ligand). Reactions of (PNP)Rh(TBE) as the source of (PNP)Rh with CHF3 and C2 HF5 produced perfluoroalkylidene complexes (PNP)RhCF2 and (PNP)RhC(F)(CF3 ). (PNP)RhCF2 could also be obtained via the reaction of (PNP)Rh(TBE) with Me3 SiCF3 /CsF, with an admixture of (PNP)Rh(C2 F4 ), where TBE = tert -butylethylene. Abstraction of fluoride from these neutral (PNP)RhC x F y complexes was successful, although only abstraction from (PNP)RhCF2 allowed unambiguous identification of the Rh product, [(PNP)RhCF] + . DFT computational studies allowed comparison of relative energies of (PNP)Rh(C2 F4 ) and [(PNP)Rh(C2 F3 )] + isomers as well as comparisons between the electronic structure of the CF2, C2 F4, and CF + complexes and their hydrocarbon analogues.